Evaluación de la producción in vitro de embriones en ovinos ( Ovis orientalis aries ) en el laboratorio de biotecnología de la reproducción de la carrera de medicina veterinaria y zootecnia de la Universidad Técnica de Cotopaxi - Jaya Saquinga, Edwin Patricio (2014)
In the present research was assessed a technological alternative that is "In vitro embryos production in sheep" was evaluated (Ovis orientalis aries) it technical and economic feasibility if is a viable option and in the future to help to preserve species embryos with originating genetic line in this place. To this effect, it suggested as objective to evaluate the in vitro embryo production in sheep in the Biotechnology Reproductive Laboratory in the Veterinary Medicine major Animal major at the Technical University of Cotopaxi ". The research methodology used was: descriptive and non-experimental because it allowed observe phenomena as they exist in their natural context, then It analyzed, for which were described by the parameters, statistical, pastels. This research was conducted in the Biotechnology reproduction Laboratory at Technical University of Cotopaxi ", it located in the Salache, neighborhood Latacunga Canton, Cotopaxi Province....